Investment Scaling-up and the Role of Government : the Case of Benin - Ghilardi, Matteo; Sola, Sergio (Washington, D.C. : International Monetary Fund, 2015)
This paper studies the fiscal implications for the Beninese economy of scaling up of public investment when the government is subject to inefficiencies on the spending and on the tax collection side. While scaling up of public investments results in higher long-run output and consumption levels, a fiscal stabilization package is required in order to preserve fiscal sustainability. A welfare analysis shows that consumers' welfare is increased when the government smoothes the fiscal adjustment via higher borrowing. Moreover, the comparison between several stabilization packages highlights the fact that higher welfare is achieved when the government relies mostly on taxation of capital as this allows higher levels of consumption to materialize earlier. Lower fiscal costs can however be achieved if the government manages to reduce inefficiency in tax collection. Finally, we consider a change in the trade regime that causes a decline in revenues. We find that the higher fiscal burden required to preserve fiscal sustainability would completely wipe out the welfare gain of higher public investments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet